Too Bad, You Were Too Late Coming In! - Legault, Marie-Josée (Unions, Equity, and the Path to Renewal, 2009)
[E]xamines the implications for unions of the federal and provincial human rights legislation and the Canadian Charter of Rights [with respect to equity]. ...[The author] warns that unless unions find acceptable ways to deal with the increasingly diverse interests of their members, conflict could ensue that could remove unions' legal right to represent certain minority intersts, as well as destroy union solidarity. [The author] describes one such conflict currently moving through the courts, which arose from the negotiation of a two-tier wage clause that is allegedly discriminatory. This is a cautionary tale that highlights the link between union revitalization and equity. --Editor's introduction
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement